The Level of Epidermal Growth Factor and Its Relationship with Leukocytes and Mast Cells in Experimental Interstitial Cystitis / Painful Bladder Syndrome - R. F. Sholan (Вестник урологии, 2020)
Introduction. The causes and mechanisms of interstitial cystitis / painful bladder syndrome (IC / PBS) remain poorly understood. The pathogenesis and the etiology of the disease is still not clearly defined. Of great interest is the role of epidermal growth factor (EGF). Due to the complexity of the pathophysiology of IC / PBS, several animal models are used to better understand the mechanisms of this disease.Purpose of the study. to determine the level of epidermal growth factor (EGF) and its association with leukocytes and mast cells of the bladder tissue in animals with experimental models of interstitial cystitis / painful bladder syndrome.Materials and methods. IC / PBS modeling was carried out on 29 individuals of white New Zealand female rabbits, which were divided into 4 groups. EGFs were determined in blood and urine by ELISA. Cellular changes in tissues were assessed by histological method.Results. A high level of EGF in urine was detected in groups 1 and 2, exceeding the intact group by 33.3% (p <0.05) and 34.6% (p <0.05), respectively. In group 1, after 14 days, EGF decreased in blood by 16.2%, in urine - by 35.5% (p <0.05). In group 2, the level of EGF increased in blood (by 61.2%, p <0.01), in urine (by 28.7%). The greatest number of lymphocytes was detected in animals of the group 2 (p <0.001). Mast cells were determined only in groups 1 and 2, and in the latter their number was greater (p <0.001) than in group 1. A strong correlation was found between the value of EGF in the blood and mast cells, as well as between the level of EGF in the urine and eosinophils in group 1. In group 2, there was a direct weak relationship between the concentration of EGF in the urine and the number of lymphocytes and mast cellsConclusion. A statistically significant increase of EGF in blood and urine was obtained in animals with simulated IC / PBS by introducing urine into the wall of the bladder. This modeling option contributed to the activation of mast cells of the bladder tissue. The association of EGF with mast cells in IC / PBS was revealed. Changes in EGF levels may be associated with IC / PBS.The study did not have sponsorship. The authors have declared no conflicts of interest.